Effects of food type on diel behaviours of common carp Cyprinus carpio in simulated aquaculture pond conditions - Rahman, Mohammad Mustafizur; Meyer, Carl G (Wiley-Blackwell, 2009)
In order to better understand behaviour patterns of common carp Cyprinus carpio in aquaculture ponds, their diel grazing, swimming, resting and schooling behaviours were observed in six 1 m2 tanks under simulated pond conditions. Each tank was fertilized to stimulate natural food production before starting experiments, and then stocked with three C. carpio. Fish behaviours were compared among three treatments: (1) tanks with plankton only, (2) tanks with plankton and benthic macroinvertebrates and (3) tanks with plankton, benthic macroinvertebrates and artificial feed. Overall C. carpio grazed more frequently during daytime than at night and exhibited the reverse pattern for non-feeding swimming behaviour. A significant negative relationship (r2 = 0·99,P <0·01, n = 48) was observed between total per cent grazing time and total per cent swimming time. Fish dispersed to graze individually during daytime but schooled at night and did not display any agonistic behaviours. Diel variations in the vertical swimming behaviour of C. carpio were related to food types available. In tanks containing plankton only, fish grazed in the water column, whereas when benthic macroinvertebrates were present, they spent more time near the tank bottom. Resting behaviour was only seen in tanks with artificial feed and even then was rare (2–5% of total time). Results suggest that C. carpio growth and feed utilization efficiency in semi-intensive aquaculture systems could be optimized by using a combination of plankton, benthic macroinvertebrates and artificial feed, and feeding fish twice per day (at c. 0730 and c. 1630 hours).